Atlantoaxial Synovial Cyst Associated with Instability in a Chihuahua. (29th March 2012) - Forterre, Franck; Vizcaino Reves, Núria; Stahl, Christina; Rupp, Stephan; Gendron, Karine
Abstract : Objective . To describe an atlantoaxial degenerative cyst associated with instability. Animal . Chihuahua, male, 5 years old. Methods . Ever since colliding with a large dog two years prior to presentation, the dog suffered recurrent episodes of intractable cervical pain. Over time, the pain attacks increased in frequency and intensity. On presentation, pain was clinically localized to the high cervical region. No neurological deficits were observed. CT and MRI revealed an atlantoaxial degenerative articular cyst associated with instability, causing cervicomedullary compressive myelopathy. On MRI the cyst appeared hypointense in T1W and hyperintense in T2-weighted sequences, with rim enhancement. The dog was treated surgically by cyst fenestration and ventral stabilization using a 1.5 mm Butterfly Locking plate and cancellous bone graft placed within the atlantoaxial joint after cartilage removal. Histological examination of a sample of the cyst wall confirmed a degenerative articular cyst. The dog recovered uneventfully after surgery and remained pain free throughout the 2-year followup. Conclusion . Atlantoaxial degenerative articular cyst associated with instability is a rare finding in dogs. Clinical Relevance . The presence of an atlantoaxial degenerative articular cyst appears not to worsen the prognosis of instability treatment. Atlantoaxial fusion and cyst fenestration may provide good long-term results.